Incorporación de una nueva línea de negocio de indumentaria femenina para la empresa Camisas Paseño de la parroquia San Antonio de Pasa - Flores Pico, Rosana Del Cisne (2023)
Working for the good of the artisans of the San Antonio de Pasa parish, improving their quality of life and looking for new sources of income, is the main reason why there was interest in the development of this project, jointly with the company Camisas Paseño it is analyzed incorporating a new line of women's clothing business in order to generate new production alternatives and adapt a new business model that is an example for the different Pymes in the sector. The San Antonio de Pasa parish is characterized by the production of shirts, mostly for the male gender, leaving aside the female gender, this being the main problem. The production system managed by the company, different business models and production systems of other companies are analyzed, accurately defining the strategy to be implemented. The design of the garment has as its main objective to meet the needs and requirements that consumers have, through technical and aesthetic processes, after defining these characteristics, the sketching process begins, where together with the owner of the company Camisas Paseño the designs will be selected. for making the collection. Next, the collection is carried out, which will be made by artisans of the parish, finally a marketing plan will be proposed with which the product will be promoted and distributed